Abigail [videorecording (DVD)] - Zhigalov, Dmitry; Boguslavskiĭ, Aleksandr; Dalakishvili, Tinatin; Marsan, Eddie; Mukhametov, Rinalʹ, 1989- (Well Go USA Entertainment, 2019)
After her father was taken years ago during an epidemic and her city's borders were closed, Abigail sets out to find him and discovers she has magical powers.